Seasonal Variations in Nutritional Profile of Notopterus notopterus: Implications for Consumer Choice, Aquaculture Diversification, and Food Security - Debnath, Chandan (Fishery Technology, 2025)
This study investigated seasonal variations in the nutritional composition of Notopterus notopterus, a potential species for aquaculture diversification in India. Samples were collected across four seasons in Tripura, India, and analyzed for proximate composition and mineral content. Significant seasonal variations were observed in protein, lipid, ash, moisture content, and mineral composition (p<0.05). Protein content peaked during the pre-monsoon season (18.2±0.3%), while the highest lipid content was observed in winter (8.5±0.2%). Calcium and phosphorus levels were highest during the monsoon season (890±18 mg/100g and 320±7 mg/100g, respectively). The results indicate that N. notopterus can be marketed as a high-quality protein source with significant micronutrient content, particularly during the pre-monsoon and monsoon seasons. These findings have implications for consumer choice, market positioning, and addressing food security in the region, emphasizing N. notopterus’ potential for sustainable aquaculture diversification and its suitability for small-scale farmers as both a nutritional resource and a complementary species to income-generating crops.